Relational Marketing Model with Determinants of Service Quality and Pricing in Creating Customer Loyalty (Case Study of Seaweed Farmer Glacillaria sp in Brebes Regency-Central Java) - Tabrani Tabrani; Dien Noviany Rahmatika; Fahmi Firmansyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine and analyze how much the contribution of service quality, pricing and relational marketing to the satisfaction and loyalty of glacillaria sp seaweed farmers in brebes district, central Java, or the services of their partners, plasma nucleus companies. The research method used is explanatory survey. Data was collected using a questionnaire, the time of data collection was cross-sectional. Data analysis using SEM. The survey identified a sample of 180 samples. The results showed that service quality, pricing and relational marketing contributed significantly to the satisfaction and loyalty of seaweed farmers. Keyword: Relational Marketing Model, Service Quality, Pricing; Loyalty